2015
DOI: 10.4172/2157-7099.1000354
|View full text |Cite
|
Sign up to set email alerts
|

Protect and Counter-attack: Nutritional Supplementation with Essential Amino acid Ratios Reduces Doxorubicin–induced Cardiotoxicity in vivo and promote Cancer Cell Death in vitro

Abstract: CommentaryHuman and experimental data show that nutritional supplementation with a specific mixture of essential amino (EAA) improves both mitochondrial function and biogenesis and reduces either ROS formation or apoptotic drive in myocytes [1][2]. Supplementation with EAA is also effective in humans when tested in patients with cardiac dysfunction [3]. Doxorubicin (Doxo), an effective cancer chemotherapy agent, causes severe cardio-toxicity due to mitochondria damage, production of reactive oxygen species (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Similarly, in vivo experiments revealed high levels of nuclear chromatin thickening and fragmentation in tumors, along with strong immunostaining for activated caspase-3 in tumors from EAARD-fed mice. This aligns with previous studies showing that EAA-mix has a cell-dependent anti-proliferative and cytotoxic effect, activating autophagy and apoptotic pathways and leading to cancer cell death without affecting non-cancer cells [7,20,26].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, in vivo experiments revealed high levels of nuclear chromatin thickening and fragmentation in tumors, along with strong immunostaining for activated caspase-3 in tumors from EAARD-fed mice. This aligns with previous studies showing that EAA-mix has a cell-dependent anti-proliferative and cytotoxic effect, activating autophagy and apoptotic pathways and leading to cancer cell death without affecting non-cancer cells [7,20,26].…”
Section: Discussionsupporting
confidence: 92%
“…We have previously explored the safety and benefits of food supplementation with a specific free AA mixture rich in EAA (EAA-mix) under various experimental conditions [5][6][7][8][9][10][11][12][13][14]. Some reports have discussed how reducing certain NEAAs (serine and glycine) and consequently increasing EAAs may impact cancer in animal settings [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works wherein rodents were fed a diet containing an excess of all EAAs in a stoichiometric ratio have shown an increase in mitochondriogenesis, improved mitochondria function, and reduced oxidative stress in skeletal muscle and heart [ 42 ]. In addition, in a pilot study, we demonstrated that supplementation of EAAs to Doxo-treated animals preserved cardiomyocytes architecture and improved the efficacy of chemotherapy [ 14 , 49 ]. More recently, we showed that a diet rich in EAAs favorably modified cell metabolism in different organs and experimental conditions [ 50 , 51 ], promoting survival [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proteasome inhibition exerted by EAA, different from that exerted by drugs like bortezumib or carfilzomib [ 22 ], is peculiarly evident and limited to cancer cells. Furthermore EAA have already been shown to be protective against doxorubicin heart damages [ 23 ], characterized by disregulation of mitochondria and autophagy [ 24 ], and being also efficient in ameliorating heart performance in aged diabetic patients affected by heart failure [ 25 ]. Introduction of serine and ornithine-αKG, in specific ratios with EAA, seems efficient to further implement the effects of altering environmental EAA/NEAA, and this not so predictable result is peculiarly efficient in eliciting activity and control of the endoplasmic reticulum proteases, and specifically by inducing cathepsin-L, mainly involved in triggering autophagy.…”
Section: Introductionmentioning
confidence: 99%